Effect of Environmental Quality and Sustainability on Visiting Interest Mediated by Tourist Recommendations in Wonorejo - Regita Cahyani; Abdul Halik; Achmad Yanu Alif Fianto (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to analyze the influence of environmental quality and sustainability on visit intention at the Mangrove Wonorejo tourism site in Surabaya, with tourist recommendation as a mediating variable. The background of this research is based on the high tourism potential of mangrove areas in coastal Surabaya, which still faces challenges in maintaining environmental quality and consistently applying sustainability principles. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents who had visited Mangrove Wonorejo, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both environmental quality and sustainability have a significant influence on visit intention. Additionally, these two variables also significantly affect tourist recommendations. Tourist recommendation is proven to significantly mediate the relationship between environmental quality and sustainability toward visit intention. These findings indicate that positive visitor experiences encourage tourists to recommend the destination to others, which in turn strengthens the intention to revisit. This research offers theoretical contributions to sustainable tourism marketing and practical recommendations for ecotourism managers to integrate conservation strategies with experience-based promotion.